VİTAMİN E UYGULANAN HİPERTİROİDİLİ SIÇANLARDA PANKREAS DOKUSUNUN İNCELENMESİ - DARIYERLİ, Nuran; SEYMEN, H. Oktay; ÖZCAN, Umut; YILMAZER, Selma; TUNÇDEMİR, Matem; KAYA, Fatma; HATEMİ, Hüsrev; YİĞİT, Günnur (Cerrahpaşa Medical Journal, 2014)
Background.- In our former experiments we observed that oxidant stress seen in hyperthyroidic conditions was reduced by vitamin E administration. In this study, examination of the pancreatic tissue was planed. Design.- Female, Wistar albino rats weighting 180-200 g. were used in groups; 1st group: Control (n=8), 2nd group: Vitamin E administered (n=9), 3rd group: Hyperthyroidic group (n=10) and 4th group: Hyperthyroidic and Vitamin E administered group (n=6). Hyperthyroidism was formed by giving L-tiroxin (0.4 mg/ 100 g food) to rats during 24 days. Vitamin E (500 mg/ kg-i.p.) is administrated in 1, 4, 7, 11, 14, 18, 21, 24 days from the beginning of the experiment. At the end of this period blood samples taken from the heart and the whole pancreatic tissue of the rats which are sacrificed under ether anesthesia. T3, T4, TSH levels were measured in the blood samples by RIA method. Pancreatic tissue was prepared for routine histologic examination. Results and Conclusion.- Insulin levels (μIU/ ml) are 8.45±5.18 in 1st group, 4.78±3.46 in 2nd group, 12.87±5.81 in 3 rd group, 3.63±2.42 in 4th group. In histologic examination of pancreatic tissues, exocrin pancreatic tissue and Langerhans islets of 1st and 3rd groups showed the same morphology. In the 4th group exocrin paranchyma destruction (acinar athrophy), lymphocyte infiltrasyon, fibrosis and fat accumulation were observed. Langerhans islets were lost or became smaller in the areas which the exocrine paranchyma was destructed. In the islets aldehide fuchcine (+) stained beta cells were seen. 2nd and 4th groups showed the same morphologic changes. Our findings suggest that insufficient insulin levels in vitamin E administered groups is related with pancreatic tissue destruction.